Behavioral Transformation of Pregnant Women in Utilizing First Pregnancy Checkups (K1) - Natsir, Nursanita; Adam, Arlin; Alim, Andi (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to understand the process of behavioral transformation among pregnant women in utilizing first pregnancy check-up services (K1) in Kadolomoko Village, Baubau City, from traditional practices to medical services, considering the social, cultural, economic, and technological factors that influence it. Research Method: This study employed a descriptive qualitative approach, utilizing data collection techniques that included in-depth interviews, field observations, and documentation. Informants were selected purposively and consisted of pregnant women, posyandu cadres, puskesmas midwives, and community leaders. Data were analyzed using a thematic approach to identify patterns of behavioral change and the factors that drove them. Results and Discussion: The study's results indicate that behavioral transformation among pregnant women occurs gradually and is influenced by health education interventions, community health worker support, the use of digital technology, and the 1,000 Days of Life (HPK) program. Although most women began to utilize medical services at health facilities, traditional practices continued to be carried out as a complement due to strong cultural values. Implications: These findings emphasize the importance of an integrative approach that respects local cultural values to support sustainable health behavior change. The practical implication is that maternal health interventions need to be designed in an adaptive, participatory, and community-based manner to achieve long-term success.